Effectiveness of psychological techniques in dental management for children with autism spectrum disorder: a systematic literature review - Ismail Nabil AlBhaisi; Marisa Shanthini Thomas Santha Kumar; Anissha Engapuram; Zaleha Shafiei; Ahmad Shuhud Irfani Zakaria; Shahida Mohd-Said; Colman McGrath (BMC, 2022)
Abstract Background A rise in the reported numbers of children with Autism Spectrum Disorder (ASD) highlights the need for dental practitioners to be more familiar with the treatment approaches for these special needs children to ensure comfortable, well-accepted and efficient management while in dental office. Aim This paper aimed to acquire a deeper understanding of some of the innovative and best approaches to managing children with ASD in dental settings. Design A systematic literature search was performed in PubMed, Scopus, Web of Science, Cochrane databases, and grey literature based on the PRISMA 2020 statement, using main keywords such as: 'management', 'dental', 'children', and 'Autism Spectrum Disorder'. Original full-text papers including randomised controlled trials (RCT) and all other designs of non-randomised controlled studies (NRS) reporting relevant intervention studies in English were included without any publication time limit. The quality of the evidence found eligible for the review were then assessed using the ROB-2 and ROBINS-I tools. Subsequently, the details of management interventions and impact of treatment approaches were compared and discussed. Results Out of the 204 articles found, 109 unrelated articles were excluded during the initial screening. The full papers of remaining 28 were retrieved and only 15 (7%) articles were eligible to be reviewed; eight RCTs with 'some concerns' and 'high risk' categories particularly concerning their randomisation design, and seven NSRs with 'serious' to 'critical' bias largely due to confounding factors. Conclusion Our review found inconclusive evidence on the strength of recent psychological and non-pharmacological approaches used to manage children with ASD in dental settings. Small sample size and lack of a control group in certain studies affected the strength of evidence and credibility of the findings. Nevertheless, this review shared informative details on some innovative approaches for better understanding of the management of children with ASD for dental professionals.